Hepatocyte nuclear factor‐1β suppresses the stemness and migration of colorectal cancer cells through promoting miR‐200b activity. Issue 8 (3rd June 2020) - Wang, Yuhui; Wei, Chengqiong; Yang, Yingying; Luo, Ailin; Zhang, Xiyang; Zheng, Dongxuan; Lu, Xi; Zhang, Kefeng; Duan, Xiaoqun; Xu, Xiaotian
Abstract: The effects of hepatocyte nuclear factors (HNFs) have been established in various tumors; however, the roles of HNF‐1β in colorectal cancer progression are never been found. In the present study, HNF‐1β expression was initially detected in clinical tissue samples and online datasets and HNF‐1β was found to be highly expressed in colorectal cancer tissues. In addition, a positive correlation existed between HNF‐1β expression and the overall survival of patients with colorectal cancer. In vitro and in vivo experiments revealed that HNF‐1β suppressed the stemness and migration of colorectal cancer cells. Combined with microRNAs (miRNAs) based on transcriptome‐sequencing analysis, mechanistic studies showed that HNF‐1β directly bound to miR‐200b promoter and thus promoted miR‐200b expression, this HNF‐1β/miR‐200b resulted in the downregulation of the expression of miR‐200b downstream effectors. Furthermore, HNF‐1β inhibits the stemness and migration of colorectal cancer cells through miR‐200b. This study reveals a novel HNF‐1β/miR‐200b axis responsible for the stemness of colorectal cancer cells.